EXPERIENCE OF RADIATION EMERGENCY RESPONSE IN THE MOSCOW REGION - E. A. Tuchkevich (Радиационная гигиена)
We present the experience of the state sanitary-epidemiological service of the Moscow region on the ensuring and implementation of preparedness for radiation emergency response. We discuss the differentiation of radiation emergency responses, depending on the character of situation development and modifying circumstances.